Pemanfaatan Channel Youtube Ustadz Adi Hidayat untuk Meningkatkan Kreativitas Mengajar Ustadz Dipondok Pesantren Al-Hikmah Bogor - Muhammad Haikal Ramadhan; Kamalludin Kamalludin; Noneng Siti Rosidah (KOLONI, 2023)
YouTube is a rapidly growing video-based social media platform. As of early 2023, YouTube had over two billion users, of which 139 million were Indonesian. This is because creating a YouTube channel and gaining a large number of views can generate income. YouTube is a platform for uploading videos, and these videos can also be downloaded. A wide variety of videos can be accessed on YouTube, including films, news, music, sports, lifestyle, gaming, vlogs, and more. YouTube allows users to upload, watch, and share videos. Based on the explanation above, it is clear that YouTube offers many benefits to its users. Therefore, this study aims to determine the benefits obtained by religious teachers at the Al-Hikmah Islamic Boarding School in Bogor from watching Ustadz Adi Hidayat's YouTube channel and also to determine how to improve the teaching creativity of religious teachers at the Al-Hikmah Islamic Boarding School in Bogor after watching Ustadz Adi Hidayat's YouTube channel. This study uses a descriptive qualitative approach. This research seeks to discover, develop, and test the truth of knowledge safely using scientific methods, which are procedures or ways of knowing something through systematic steps. Therefore, research methods are essential in scientific research, as the quality and validity of scientific research results are determined by the accuracy of the research method chosen.